Development of excellency-based curriculum: Evidences from integrated Islamic primary schools in Kediri - Suyitno Suyitno; Ariesty Fujiastuti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This research was aimed to describe strategies of excellent learning program and curriculum development plan, learning and curriculum implementation, and evaluation of learning and curriculum. This research used qualitative multisite study design with interactive analysis model (Miles and Hubberman, 1994). This research resulted: Integrated strategy of community need assesment, team formulation, work meetings and shared decisions, and teachers development; Mental and physical process focused, flexible and enjoyable learning model, and right brain based Al-Qur” -the so called WAFA, daily test with Al Qur’an Recitation Repeatation Model, the so-called Munakosyah Tahfidz and Tilawah test, Criterion Reference Measurement mid and final tests.